Epistemologi the Holy Qur’an Arabic Text with English Translation and Commentary Karya Maulana Muhammad Ali - Apri Cahyani, Fatkha; Nur Aini; Abdul Jabpar (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
The Holy Qur'an Arabic Text with English Translation and Commentary is one of the English translations and exegesis born in the 20th century. This 30-juz translation and tafsir became the first translation and interpretation in English by the founding Muslim scholar of Ahmadiyya Lahore, Maulana Muhammad Ali. The translation and interpretation of The Holy Qur'an is also the main work that references the Ahmadiyya mission in translating and interpreting the Qur'an into various languages, such as Malay, Javanese, and German. As is well known, that the product of tafsir is the result of man's understanding of the Qur'an. There are several things that cannot be separated from interpretation, including the tendency of mufasir, socio-cultural conditions faced by mufasir, the context in which interpretation appears, the background of interpretation, and so on. This has implications for differences in interpretation in terms of patterns, methods and approaches. To know this, epistemological studies are needed. Departing from the explanation above, the author applies the theory of epistemology to dissect the Holy Qur'an by Maulana Muhammad Ali in three aspects, namely the source, nature, and validity of interpretation. Keywords: Epistemology, The Holy Qur'an Arabic Text with English Translation and Commentary, Maulana Muhammad Ali